Pengembangan Buku Bacaan pada Mata Pelajaran IPS untuk Meningkatkan Aktivitas Belajar - Lia Apriyanti; Pargito Pargito; Pujiati Pujiati (Faculty of Teacher Training and Education, University of Lampung, 2017)
This study aims to: 1) produce reading books in social study that can be used as an alternative to improve learning activity of students and 2) determine the effectiveness of reading books in social studies. The Research and Develompent (R D) is used in this study. The process of developing reading book entitled